Análisis de los costos de producción de las microempresas dedicadas al cultivo de claveles en el barrio Patután de la parroquia Eloy Alfaro de la provincia de Cotopaxi. - Caisaluisa Llumiquinga, Estefany Adriana (2019)
Nowadays, agricultural activity has become the main source of economy for the producers at Patután neighborhood in Cotopaxi Province, who have considered the carnation cultivation an activity to generate income, many farmers do not know how to evaluate the supplies, causing an empirical management of material, economic and human resources. With this perspective, it is proposed to carry out an analysis of carnation production costs through a comparison between two representative microenterprises of the sector, in order to establish the level of impact on profitability obtained at the end of the production process. In the first instance, the methodology of quantitative approach was used with the purpose of collecting real data on the values of the expenses incurred and then use the field research modality to establish contact with the owners and directly visualize each of the processes involved in the production. After that, in the development of the methodological framework information was collected from primary and secondary sources through documentary research, while the descriptive method was used to detail the financial situation. To project the difference between the profitability generated by the Micro enterprises "Virgen Santa Rosa de Patután" and "Clara Llumiquinga", depending on the costs they produce, the technique of the simulation of the process cost system was used, it allowed to identify the different costs and determine their real value. The results of this research show the impact that costs have on the usefulness of the microenterprises, finding a difference of $ 450.00, it decreases the income margin, so "Clara Llumiquinga" Micro enterprise acquires products at high prices that contribute enough nutrients to obtain a high quality product. It is also due to the constant application of the products that control pests and diseases to improve the plant development. For this reason, micro enterprises must establish mechanisms for measuring and controlling costs to make better decisions in future productions, reducing costs to generate greater profitability.